Zarządzanie kapitałem obrotowym w wybranym przedsiębiorstwie gospodarki żywnościowej - Szczecińska, Beata (Managing of Working Capital in Food Industry Company, 2006)
This article presents the level and structure of working capital in a food industry company. Competitiveness of a company depends on its financial power. During the researched period (2002-2004) the company's working capital was conducted in a conservative way. Data analysis shows that liquidity of this company had increased till 2004. This joint stock company had positive value of working capital in all analized years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 378-383